DOP49 Context-dependent roles of High-mobility group box 1 (HMGB1) during intestinal inflammation and carcinogenesis. (21st January 2022) - Zierz, E; Foelsch, K; Pelczar, P; Qi, M; Alawi, M; Clauditz, T; Gagliani, N; Huber, S; Huebener, P; ,
Abstract: Background: HMGB1 is a ubiquitously expressed nucleoprotein with proinflammatory functions following cellular release. The protein is passively released during tissue necrosis, acting as a damage-associated molecular pattern, but can also be actively secreted by immune cells. Stool and serum HMGB1 levels have been suggested as markers of both inflammatory bowel disease (IBD) activity and colorectal cancer (CRC) invasiveness, and antibody-mediated HMGB1 neutralization was beneficial in animal models of IBD. We explored context-dependent functions of HMGB1 in the injured intestine using novel experimental mice with cell-specific genetic HMGB1 deficiency. Methods: To circumvent the postnatal lethality of global HMGB1 deficiency in animals, we used the Cre-lox system to generate enterocyte-specific ( Hmgb1 ΔIEC, Villin-Cre) and myeloid cell-specific ( Hmgb1 ΔLysM, LysM-Cre) HMGB1-knockout mice. Animals were subjected to well-established models of acute (DSS, Citrobacter rodentium ) and chronic (AOM+DSS, CD45RBhigh T cell transfer colitis, Apc +/min ) intestinal injury, followed by clinical, endoscopic, histological and molecular analysis. HMGB1 expression was assessed in human IBD and CRC specimens. Results: IBD and CRC biopsies exhibited high levels of HMGB1 expression in epithelia, immune cells, tumor cells and the peritumoral stroma. HMGB1 deficiency from enterocytes and myeloid cells did not alter Citrobacter- or T cell transfer-induced enterocolitis, when epithelial injury was comparably low. In contrast, Hmgb1 ΔIEC mice exhibited aggravated DSS-induced colitis, as evidenced by severe weight loss as well as exacerbated neutrophil- and monocyte-driven mucosal inflammation compared to Hmgb1 f/f . Whole tissue RNA sequencing indicated defective cellular proliferation in injured Hmgb1 ΔIEC intestines. In the AOM+DSS-model, Hmgb1 ΔIEC had a comparable tumor burden to Hmgb1 f/f, whereas Hmgb1 ΔLysM had significantly fewer and smaller tumors, potentially linked to metabolic alterations in the tumor micromilieu. In the Apc +/min model, enterocyte HMGB1 deficiency effectuated more and larger tumors, whereas leukocyte HMGB1 did not affect tumor load. Conclusion: Contrasting antibody-mediated HMGB1 neutralization in animal models of IBD, our findings from genetic HMGB1 deletion studies reveal a critical role of enterocyte HMGB1 in the maintenance of the intestinal barrier during severe colitis. Impaired epithelial regeneration or inefficient local immune cell expansion in Hmgb1 ΔIEC may account for the aggravated phenotype. HMGB1 from enterocytes and immune cells context-dependently affect maladaptive intestinal would healing, potentially mediated by cell-intrinsic and -extrinsic mechanisms that warrant further investigation.